Implementation of Sharia Accounting in Fintech: A Review of Sharia Compliance and Regulatory Framework - Nani Wahyuni; Taufik Akbar (Proceeding International Annual Conference Economics, Management, Business, and Accounting, 2025)
This study explores the integration of Islamic accounting in fintech and its impact on Sharia compliance within Islamic financial institutions. As fintech rapidly evolves, a significant gap has emerged between innovation and existing regulatory frameworks, posing a major challenge in ensuring full adherence to Sharia principles. The research applies the Tawḥīd String Relationship (TSR) theory, which links economic activities to the Islamic concept of monotheism (tawḥīd), along with maqāṣid al-sharīʿah to gain a broader understanding of the objectives of Islamic law. The findings reveal that while fintech brings notable advancements—such as digital payments, peer-to-peer (P2P) lending, and Sharia-compliant investment platforms—these innovations must be carefully aligned with Islamic principles to avoid elements such as ribā (usury), gharar (uncertainty), and maysir (gambling). The study also highlights the urgent need for a comprehensive regulatory framework, supported by active oversight from authorities like Indonesia’s Financial Services Authority (OJK) and Sharia Supervisory Boards (DPS). Overall, this research offers insights into how Sharia-compliant fintech can enhance financial inclusion, consumer protection, and economic justice, while also identifying the risks that may arise from unregulated innovation. The novelty of this study lies in its integration of TSR and maqāṣid al-sharīʿah, proposing a holistic approach to fintech regulation.